MATEM: A unified framework based on trust and MCDM for assuring security, reliability and QoS in DTN routing. (15th February 2018) - Paul, Amrita Bose; Biswas, Santosh; Nandi, Sukumar; Chakraborty, Sandip
Abstract: The research work presented in this paper aims at finding new ways of ensuring security, pervasive reliability and Quality of Service (QoS) to Delay Tolerant Network (DTN) routing while exploiting the functionality and characteristics of mobile devices in a hostile networking environment. The final outcome is a unified framework, called "Multi-Attribute Trust Evaluation and Management" (MATEM), which can be flexibly integrated with a large family of existing routing protocols to ensure secure, reliable and pervasive communication over a hostile DTN. The effectiveness and robustness of MATEM against different security metrics, viz., attack detection, false positive and false negative rates are assessed in the presence of bad-mouthing, good-mouthing, and selfish attacks. The framework efficiency is also evaluated through extensive simulations study and a comparative analysis with other existing frameworks are carried out in terms of different routing metrics, viz., message delivery ratio, delivery latency, and delivery cost . Furthermore, a user experiment is conducted to investigate the impact of MATEM on a real testbed forming a DTN environment. Results generated from simulations and the real testbed verified the usability and user acceptance of MATEM in DTN.